The UHPLC-DAD fingerprinting method for analysis of extracellular metabolites of fungi of the genus Geosmithia (Acomycota: Hypocreales) - Tylová, Tereza; Kolařík, Miroslav; Olšovská, Jana (Analytical and bioanalytical chemistry, 2011)
A new simple ultra-high-performance liquid chromatography method with diode array detection (UHPLC-DAD) was developed for chemical fingerprinting analysis of extracellular metabolites in fermentation broth of Geosmithia spp. The SPE method employing Oasis MCX strong cation-exchange mixed-mode polymeric sorbent was chosen for extraction of the metabolites. The analyses were performed on an Acquity UPLC BEH C18 column (100 × 2.1 mm i.d.; particle size, 1.7 μm; Waters) using a gradient elution program with an aqueous solution of trifluoroacetic acid and acetonitrile as the mobile phase. The applicability of the method was proved by analysis of 38 strains produced by different species and isolated from different sources (hosts). The results revealed the correlation of obtained UHPLC-DAD fingerprints with taxonomical identity.
Keywords: reprodukovatelnost výsledků; Hypocreales; Chromatography, High Pressure Liquid; Solid Phase Extraction; extrakce na pevné fázi; Fermentation; fermentace; Reproducibility of Results; vysokoúčinná kapalinová chromatografie